Penggelapan Penggunaan Jabatan di Lingkungan Perbankan dalam Menggandakan Rekening Bank - Agus Wija Atmaja; I Nyoman Gede Sugiartha; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2022)
This study aims to analyze and describe the embezzlement of the use of positions in the banking environment in doubling bank accounts. With the development of human civilization and technology, traditional methods and procedures are no longer used in this crime of embezzlement. One of the most modern ways is embezzlement by duplicating bank accounts with other names. This, but from the same owner. According to his explanation, there are two main problems. Namely, the regulation of criminal acts and criminal sanctions for embezzlement against the dual use of bank accounts. This study uses a normative legal study using a legal conceptual approach. The findings show that Article 374 reflects the regulation of the crime of embezzlement by using authorized bank accounts, as well as other crimes where the crime of embezzlement is mostly the crime of embezzlement. Will be sentenced to five years in prison for embezzlement of bank accounts, which exacerbates other elements of criminal threats in accordance with Article 374 of the Criminal Code.